2019
DOI: 10.1002/jca.21746
|View full text |Cite
|
Sign up to set email alerts
|

The combination of granulocyte‐monocyte apheresis and vedolizumab: A new treatment option for ulcerative colitis?

Abstract: Objectives To assess the effectiveness and safety of combining granulocyte‐monocyte apheresis (GMA) and vedolizumab (VDZ) in patients with refractory ulcerative colitis (UC). Methods This retrospective, multicentre pilot study included all UC patients receiving both GMA and VDZ. We recorded data on GMA sessions, demographic characteristics, and clinical response. Effectiveness was assessed 1 and 6 months after finishing the GMA using the partial Mayo score, C‐reactive protein, and fecal calprotectin levels. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In such a situation, combined treatment with GMA and VDZ has been attempted in patients with refractory UC and was reported to be effective. 23 Therefore, in this case who had experienced LOR to anti-TNFα, VED appeared to be effective for intestinal IBD lesions, but with the appearance of PG, we opted for prednisolone and GMA combination therapy. In particular, GMA has a very favorable safety profile, with adverse side effects being uncommon and never severe.…”
Section: Discussionmentioning
confidence: 96%
“…In such a situation, combined treatment with GMA and VDZ has been attempted in patients with refractory UC and was reported to be effective. 23 Therefore, in this case who had experienced LOR to anti-TNFα, VED appeared to be effective for intestinal IBD lesions, but with the appearance of PG, we opted for prednisolone and GMA combination therapy. In particular, GMA has a very favorable safety profile, with adverse side effects being uncommon and never severe.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism underlying GMA involves the Adacolumn, which is filled with cellulose acetate (CA) beads, interacting with fragment crystallizable‐gamma receptor (FcγR) expressed at the surface of activated leukocytes and selectively adsorbing granulocytes and monocytes from the systemic circulation 2 . Numerous reports have described the clinical efficacy and safety of GMA in patients with active UC 3‐22 . Previous reports have demonstrated that patients who were most likely to respond to GMA tended to be first attack cases and were steroid‐naïve with short disease duration and low disease activity 9‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…In eight adult patients with UC, with primary or secondary loss of response to VDZ, and previously treated with anti-TNF agents, partial Mayo score improved after 1 and 6 months of combining GMA and VDZ. 34 In another adult patient with refractory UC and no response to VDZ, clinical remission was achieved with the combination of GMA and VDZ. 35 …”
Section: Case Seriesmentioning
confidence: 99%